Determinantes na obtenção da ocupação na área do curso de graduação e/ou do aumento da renda: um estudo de caso sobre os egressos dos cursos de graduação da UFC - Moura Filho, Sérgio Ricardo Braga (2014)
The main point of this research was to identify which factors (concerning to personal aspects, academic training and occupational character) influence on the probabilities related to occupation in the areas of graduation courses and income growth on the egresses from the graduated students at the Universidade Federal do Ceará. In order to achieve this goal, the applied methodology was the descriptive and explanatory research, also quantitative, using primary data, obtained through questionnaires applied to 597 graduated students in 2011, then acquiring a sample of 100 contributors, besides secondary data, spreadsheets containing general and individual – API (Academic performance index) from the graduated students of Pro-Reitoria de Graduação database. The result analysis method was an econometric model logit of binary choice. Concerning to the answers, it was verified that the most part of the graduated students in analysis are engaged in areas related to their graduation courses and have increased their incomes. From the estimated results, it could be verified that 4(four) explanatory variants influence positively (increase) on chances of a given graduated student to get an occupation in a field related to his graduation course: ethnicity, previous professional experience, another graduation course and the course time. Further, it could be verified that 3 (three) explanatory variables increase the probabilities of getting an income raise, which are: general-API, working in an area related to the graduation course and another graduation course. As for the age-variable, it is considered to influence negatively (diminish) on the probability of obtaining an income raise. Besides, the 2(two) Logit estimated models for occupation and income showed results which were consistent with the reality, and was validated the research hypothesis which states that the general API of UFC graduate students is a determining factor in getting the increased income of the same.